Hereditary breast and ovarian cancer. - Sullcahuamán Allende, Yasser (2015)
Cancer is considered a public health issue. Genetic and molecular biology studies done in this area can define cancer as a genetic disease. Therefore, breast and ovarian cancer can be classified in: a) sporadic cancer, including 70-80% of cases; b) familial, 15- 30% of cases; and c) hereditary, 5-10%. Since these groups have different clinical manifestations and molecular features, it is necessary to create preventive measures, provide adequate management and most importantly, offer genetic counseling.